2019
DOI: 10.1002/cpt.1301
|View full text |Cite
|
Sign up to set email alerts
|

Protein Abundance of Clinically Relevant Drug Transporters in the Human Liver and Intestine: A Comparative Analysis in Paired Tissue Specimens

Abstract: Bioavailability of orally administered drugs is partly determined by function of drug transporters in the liver and intestine. Therefore, we explored adenosine triphosphate–binding cassette (ABC) and solute carriers family transporters expression (quantitative polymerase chain reaction) and protein abundance (liquid chromatography tandem mass spectrometry (LC‐MS/MS)) in human liver and duodenum, jejunum, ileum, and colon in paired tissue specimens from nine organ donors. The transporter proteins were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 50 publications
(120 reference statements)
8
92
1
Order By: Relevance
“…The expression of OAT7 and MRP2 was significantly decreased from steatosis to NASH livers. Surrogate peptides of BCRP and MRP4 were not detectable in the liver samples with the current methodology, which is not unexpected given the very low expression of these proteins in human livers as noted in other reports …”
Section: Resultssupporting
confidence: 81%
“…The expression of OAT7 and MRP2 was significantly decreased from steatosis to NASH livers. Surrogate peptides of BCRP and MRP4 were not detectable in the liver samples with the current methodology, which is not unexpected given the very low expression of these proteins in human livers as noted in other reports …”
Section: Resultssupporting
confidence: 81%
“…SLC16A1 expression in the human liver measured at the mRNA level has been evidenced by Williams et al [7]. Our studies demonstrated a presence of not only mRNA, but also the MCT1 protein in human livers, in both organ donors as well as metastatic liver disease hepatic tissues [4,8]. Metastatic livers were characterized by a significantly elevated content of SLC16A1 mRNA transcripts in comparison to donor samples, but comparable abundance of MCT1 protein.…”
Section: Introductionsupporting
confidence: 75%
“…The transporter facilitates either the influx or efflux of the substrates, depending on substrate and H + -concentration gradients [1]. SLC16A1 is expressed in tissues that rely on the efflux or uptake of energy metabolites, based on the energetic profile (e.g., brain, heart, kidney, lungs, liver, muscle, placenta, and erythrocytes), but also in the gastrointestinal tract to support the absorption of short chain fatty acids, such as acetate, propionate, or butyrate [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…MRP2 was found to be the most abundant ABC transporter, whereas OATP2B1 was the most abundant SLC transporter. Conflicting reports are found in the literature with respect to the rank order of abundances of the transporters quantified in this study Drozdzik et al, 2014Drozdzik et al, , 2019Miyauchi et al, 2016). This can be due to differences in sample preparation techniques and proteomic and interindividual variability Drozdzik et al, 2014;Harwood et al, 2014Harwood et al, , 2016.…”
mentioning
confidence: 61%